Efficacy and safety of low-dose rituximab in the treatment of myasthenia gravis: a systemic review and meta-analysis - Yang, Xishuai; Zhang, Wei; Guo, Junhong; Ma, Chunlin; Li, Bingxia (Frontiers in Neurology, 2024)
Rituximab (RTX) is a monoclonal antibody that has been increasingly used in treating myasthenia gravis (MG). In most of studies, the therapeutics protocol was similar to that adopted for B cell lymphoma, increasing number of studies have tried to explore the efficacy of low-dose RTX in MG. However, the beneficial effects of low-dose RTX in MG are still a critical debating question.This study was conducted according to PRISMA (Preferred Reporting Items for Systemic review and Meta-Analysis) statement. Two reviewers (Xishuai Yang and Bingxia Li) independently searched the PubMed, MEDLINE, EMBASE, Web of Science, Cochrane library, CNKI (China National Knowledge Infrastructure). Metaanalysis via representative forest plots was conducted for "Improved clinical status", Quantitative Myasthenia Gravis (QMG) score change pre and post-treatment.A total of 17 studies involving 292 patients were included in the meta-analysis. Improvement in clinical status was observed in 91% of patients at the final follow-up after therapy (95%CI:84%-96%, P<0.001). The QMG score showed a significant reduction following treatment, with a standardized mean difference (SMD) of -1.69 (95%